2015
DOI: 10.3109/09593985.2014.994151
|View full text |Cite
|
Sign up to set email alerts
|

Positive pressure – analysing the effect of the addition of non-invasive ventilation (NIV) to home airway clearance techniques (ACT) in adult cystic fibrosis (CF) patients

Abstract: This study is limited by small numbers; however, trends towards less hospital admissions and greater patient ease while using NIV with ACT warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 16 publications
0
18
2
Order By: Relevance
“…There were trends for lower reported levels of breathlessness and fatigue with the use of NIV, but these did not reach significance. This differs from our previously reported results where subjects did subjectively rate NIV-supported ACT significantly higher for EoC and reduced effort13; however, those results were from a more severe patient group (median FEV 1 26%) over a 1-year period. Several of the participants of the current study commented that they felt NIV would be useful for them if they were more unwell, breathless or unable to expectorate, as they felt it would be more supportive at that time, which may then provide more comparable data.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There were trends for lower reported levels of breathlessness and fatigue with the use of NIV, but these did not reach significance. This differs from our previously reported results where subjects did subjectively rate NIV-supported ACT significantly higher for EoC and reduced effort13; however, those results were from a more severe patient group (median FEV 1 26%) over a 1-year period. Several of the participants of the current study commented that they felt NIV would be useful for them if they were more unwell, breathless or unable to expectorate, as they felt it would be more supportive at that time, which may then provide more comparable data.…”
Section: Discussioncontrasting
confidence: 99%
“…The research question stemmed from previously published research interviews completed with CF patient users of NIV for ACT,13 which on further discussion with these patients the authors felt was important to try and answer objectively. Patients with CF from the Royal Brompton Hospital were involved in designing the methodology to try and answer the question of whether sputum clearance changed with the addition of NIV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Standford et al looked at a one-year period following the addition of NIV to airway clearance techniques (ACT) and demonstrated statistically significant improvements in ease of patient report of airway clearance and reduced effort during ACT. 28 This study analyzed objective measures such as lung function and frequency of use of IV antibiotics, as well as patient reported measures of fatigue and breathlessness. 28 Patients reported significant improvement in fatigue and breathlessness, which would lead to improved quality of life.…”
Section: Benefits Of Niv For Cf Patientsmentioning
confidence: 99%
“…In stable CF patients with awake hypercapnia, a six week trial of nocturnal noninvasive ventilation showed improved nocturnal hypoventilation and peak exercise capacity without improving lung function or awake hypercapnia 64 . Noninvasive ventilation has also been evaluated in cystic fibrosis patients as an adjunct to airway clearance techniques, 65,66 particularly in patients having trouble expectorating sputum. 65 The rationale is that in patients with severe lung disease, airway clearance therapy results in energy expenditure and use of noninvasive ventilation could allow for decreased work of breathing and fatigue.…”
Section: Treatmentmentioning
confidence: 99%